Pengaruh Kenyamanan, Kepercayaan, dan Harga Terhadap Minat Mahasisiwi FEBI IAIN Langsa Berbelanja Online Menggunakan Akad Salam - Faisal Umardani Hasibuan; Zella Safira (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2020)
The purpose of this study was to determine how the effect of convenience, trust and price on comfort of islamic economics and business faculty students online shopping with as-salam contract.This type of research is kuantitatif recearch. The samples in this study were 85 respondens from students have been shopping online with as-salam contract The sampling tecnique using simple random sampling . methods of data collection by questionnaire. Data analysis using multiple regression analysis.The results showed that in the F test of regression conducted found that all variables that include convenience,trust and price simultaneously positive and significant effect  the comfort online shopping with as-salam contract. While the results of t tests conducted that partially influential variables are the convenience and price positive and significant effect agains comfort online shopping with as-salam contract, while the partial trust variables have positive effect so not significant on comfort online shopping with as-salam contract.